Combining mindfulness and cognitive training in children with attention deficit hyperactivity disorder: study protocol of a pilot randomized controlled trial (the NeuroMind study) - Badia-Aguarón, Tania; Royuela-Colomer, Estíbaliz; Pera-Guardiola, Vanessa; Vergés-Balasch, Pere; Cebolla, Ausiàs; Luciano, Juan V.; Soler, Joaquim; Feliu-Soler, Albert; Huguet Miguel, Anna (Frontiers in Psychology, 2024)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) has a global mean prevalence of 5%. Cognitive Training (CT) and Mindfulness-Based Interventions (MBIs) have shown promising results in managing ADHD symptoms, but they are not its Treatment-As-Usual (TAU). The NeuroMind Study aims to evaluate the preliminary effectiveness and feasibility of three interventions: Mindfulness for Health (M4H), CT using the NeuronUP® platform (CT), and a combination of both, Mindfulness Cognitive Training (MCT). There is empirical evidence supporting the effectiveness of the M4H and NeuronUP® platform; however, this study explores for the first time the effectiveness of MCT and CT, as well as the integration of M4H into TAU. The objectives of this 5-month Randomized Controlled Trial (RCT) are: 1) To analyze the preliminary effectiveness and feasibility of M4H, CT or a combination of both (MCT) added to TAU for children with ADHD; 2) To evaluate the role of psychological process variables (mindfulness and emotional regulation) as mediators of 5-month follow-up clinical outcomes; 3) To preliminarily explore whether specific sociodemographic and clinical characteristics can predict the short-and medium-term clinical response to the specific treatments.Methods and Analysis: Participants will be 120 children (7 to 12 years) with ADHD recruited at Child and Adolescent Mental Health Service (CAMHS) Sant Joan de Déu Terres de Lleida (Spain) randomly allocated to one of the four study arms: TAU vs. TAU + CT vs. TAU + M4H vs. TAU + MCT. An assessment to collect ADHD symptoms, Executive Functions (EF), comorbid symptoms and global functioning will be conducted pre-intervention, post-intervention (2 months after baseline) and at the 5-month follow-up. Linear mixed models and mediational models will be computed.Discussion: If the preliminary effectiveness and feasibility of the MCT are demonstrated, this study could be a preliminary basis to do a full RCT with a larger sample to definitively validate the intervention. The MCT could be applied in clinical practice if it is definitively validated.This study has been approved by the Sant Joan de Déu Foundation Ethics Committee. The results will be disseminated through peer-reviewed journals, conference presentations, social media and community engagement activities. Trial registration number: NCT05937347 (ClinicalTrials.gov).